Determination of liver volume by the use of a gamma camera connected with 1600 or 4096 channel analyser in diffuse liver diseases. Issue 4 (April 1976) - Fujii, M; Mukai, T; Yamamoto, T; Wakisaka, G
Abstract : A method of in vivo calculation of liver volume using a gamma camera and a 1600 or 4096 channel analyser is described. Topographically, the maximum thickness giving the highest counts in matrix data in the right anterior oblique projection is measured as the maximum breadth in the right posterior oblique projection. Then the total counts given by the liver can be transformed to the volume. The necropsy criteria indicated that the errors were between –11-9 +/- 14-7% in 13 cases by the use of 198Au-colloid. In 20 selected normal control subjects, the mean of measured liver volumes was 779 +/- 99 cm3/m2 of surface area. The volumetric calculation using 99mTc-Sn-colloid or 99mTc-phytate was compared with 198Au-colloid in the same patients. The results with 99mTc-Sn-colloid were well correlated with those with 198Au-colloid, but the results with 99mTc-phytate and 198Au-colloid were almost equal. It was concluded that, excluding rare severe cases of liver cirrhosis, liver volume can be measured with reasonable accuracy.